Measurement of the lifetimes of promptly produced Ω0c and Ξ0c baryons; Science Bulletin; Vol. 67, iss. 5 - Aaij R. Roel; Abdelmotteleb A. S.; Beteta C. A. Carlos Abellan; Ackernley T.; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2022, 2022)
Title screen